Frequency and Risk Factors of Blood Transfusion in Abdominoplasty in Post–Bariatric Surgery Patients: Data from the Nationwide Inpatient Sample. Issue 5 (May 2015) - Masoomi, Hossein; Rimler, Jonathan; Wirth, Garrett A.; Lee, Christine; Paydar, Keyianoosh Z.; Evans, Gregory R. D.
Abstract : Background: There are limited data regarding blood transfusion following abdominoplasty, especially in post–bariatric surgery patients. The purpose of this study was to evaluate (1) the frequency and outcomes of blood transfusion in post–bariatric surgery patients undergoing abdominoplasty and (2) the predictive risk factors of blood transfusion in this patient population. Methods: Using the Nationwide Inpatient Sample database, the authors examined the clinical data of patients with a history of bariatric surgery who underwent abdominoplasty from 2007 to 2011 in the United States. Results: A total of 20, 130 post–bariatric surgery patients underwent abdominoplasty during this period. Overall, 1871 patients (9.3 percent) received blood transfusion. Chronic anemia patients had the highest rate of blood transfusion (25.6 percent). Post–bariatric surgery patients who received blood transfusion experienced a significantly higher complication rate (10.1 percent versus 4.8 percent; p < 0.01), longer mean hospital stay (4.0 days versus 2.4 days; p < 0.01), and higher mean total hospital charges (49, 116 versus 33, 927; p < 0.01). Multivariate regression analysis showed that deficiency anemia (adjusted OR, 3.8), congestive heart failure (adjusted OR, 2.4), concurrent breast reduction (adjusted OR, 1.5), diabetes mellitus (adjusted OR, 1.4), coronary artery disease (adjusted OR, 1.4), African American race (adjusted OR, 1.4), Hispanic race (adjusted OR, 1.4), and female sex (adjusted OR, 1.3) were all independent risk factors for blood transfusion. Conclusions: The blood transfusion rate in post–bariatric surgery abdominoplasty patients is not insignificant. Chronic anemia and congestive heart failure are the two major predictors of transfusion. Modifying risk factors such as anemia before abdominoplasty might significantly decrease the possibility of blood transfusion. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.